Հայոց մշակութային ինքնավարության ծրագիրը Վրաստանի Հանրապետությունում 1920 թ. - Մաիլյան, Բենիամին (Ասողիկ հրատ.)
After the announcement of Georgia's independence а 400,000 Armenian Community appeared in its domain, that was in need of status definition in the relations with the Georgien State. According to the activists of Armenian national council in Georgia it would have to assist cultural autonomy of Armeniens, consisting part of which was the idea of the National School.
Keywords: Մշակույթ; Պատմություն